The politicization of PISA in evidence-based policy discourses - Volante, Louis; Mattei, Paola (Policy Futures in Education, 2024)
Education reform efforts stemming from the Programme in International Student Achievement have strengthened in recent years, particularly in response to the growth of global references societies – high achieving educational jurisdictions such as Finland, Hong Kong-China, and more recently Estonia and Singapore. Despite political rhetoric, evidence-based policy development associated with this international benchmark measure is rarely, if ever, a neutral enterprise that is guided by the best available evidence. Indeed, political discourse and policy framing surrounding PISA often results in the selective use of results to justify contested policy reforms. Brief cases from Japan, Sweden, and Canada illustrate how national policies have been adopted that are not grounded, and may even run counter, to research findings. The discussion examines the politicization of PISA and its symbolic role in adding legitimacy to education reform agendas. Collectively, the analysis offers an alternative perspective to the popular notion that PISA guides evidence-based decision-making.
Publisher: SAGE Publications